11 May 2024 Superstorm Ionospheric Observations in the Continental US - Haystack Observatory; Zhang, Shunrong; Foster, John; Bush, Dan (Zenodo, 2024)
May11_150km.mat: MATLAB save file - Ionospheric total electron content data from worldwide GNSS receivers, processed by MIT Haystack Observatory through the Millstone Hill Geospace Facility. Data is line of sight and conversion assumes a non-standard 150 km ionospheric pierce point. Direct permanent link: Anthea Coster, MIT/Haystack Observatory. (2024) Data from the CEDAR Madrigal database. Available from https://w3id.org/cedar?experiment_list=experiments4/2024/gps/11may24&file_list=los_20240511.001.h5 GPS TEC data products and access through the Madrigal distributed datasystem are provided to the community by the Massachusetts Institute ofTechnology under support from US National Science Foundation grantAGS-1952737. Data for the TEC processing is provided from the following organizations: UNAVCO, Scripps Orbit and Permanent ArrayCenter, Institut Geographique National, France, International GNSSService, The Crustal Dynamics Data Information System (CDDIS),National Geodetic Survey, Instituto Brasileiro de Geografia eEstatística, RAMSAC CORS of Instituto Geográfico Nacional de laRepública Argentina, Arecibo Observatory, Low-Latitude IonosphericSensor Network (LISN), Canadian High Arctic Ionospheric Network,Institute of Geology and Geophysics, Chinese Academy of Sciences,China Meteorology Administration, Centro di Ricerche Sismologiche,Système d'Observation du Niveau des Eaux Littorales (SONEL), RENAG:REseau NAtional GNSS permanent - https://doi.org/10.15778/resif.rg,GeoNet - the official source of geological hazard information for NewZealand, Finnish Meteorological Institute, SWEPOS - Sweden,Hartebeesthoek Radio Astronomy Observatory, TrigNet Web Application,South Africa, Australian Space Weather Services, RETE INTEGRATANAZIONALE GPS, Estonian Land Board, TU Delft, Western CanadaDeformation Array, EUREF Permanent GNSS Network, GeoDAF: Geodetic DataArchiving Facility, African Geodetic Reference Frame (AFREF),Kartverket - Norwegian Mapping Authority, Geoscience Australia, IGSData Center of Wuhan University, ...